Role of Specific Playing Position on Various Anthropometric, Body Composition and Physical Fitness Parameters of Indian Male Sepak Takraw Players - Sarkar, Surojit; Dasgupta, Suvam; Chatterjee, Subhra; Meitei, K Kosana; Bandyopadhyay, Amit; Dey, Swapan Kumar (International Journal of Sport Studies for Health, 2019)
Background: Anthropometric and physiologic properties have influence on exercise performance in sepak takraw and physiological profiles of athletes differ between sports and playing positions.Objectives: Present study was aimed to determine the effect of playing position on anthropometric, body composition and physical fitness parameters in young male sepak takraw players.Methods: The cross-sectional study was conducted on three positional groups of total 44 male Indian sepak takraw players (spiker/killer, n = 14; tekong, n = 14; and feeder, n = 16) of national level. Anthropometric parameters, body composition profile, physical fitness variables including 30m flying, 6X10m shuttle run, vertical jump, sit up, endurance and anaerobic power were assessed by following standard protocols.Results: Significant differences were observed in height, weight and leg length among the positional groups. Almost all body composition parameters were significantly (P < 0.01) higher among ‘tekong’ position except fat mass. Handgrip strength, back strength, vertical jump, sit up, VO2max, explosive leg power and maximum anaerobic power were found to be significantly differed among the three positional groups of sepak takraw. Regression prediction model identified back strength (P = 0.034), peak explosive power (P < 0.001) and leg length (P < 0.001) as the significant predictor of vertical jump (R2 = 0.930 and P < 0.001).Conclusions: Players of ‘tekong’ position were better in anthropometric and body composition profiles than ‘spiker and feeder’. Whereas, ‘spiker’ position was found to have higher back strength, explosive power, vertical jump and sit up abilities. Regression model identifies back strength, peak explosive power and leg length as the significant predictors of performance in sepak takraw.